HUBUNGAN PENGETAHUAN DAN SIKAP MURID SD TERHADAP PERSONAL HYGIENE - Vetri Nathalia; Gito Vakol (Jurnal Akademika Baiturrahim Jambi, 2019)
Personal hygiene is a way of maintaining one's personal health both physically and psychologically which aims to prevent the outbreak of illness and improve health status. Data from the Padang Panjang City Health Office, the highest percentage of personal hygiene problems occurred at Merapi Padang Panjang Elementary School at 68%. The purpose of this study was to determine the relationship between students' knowledge and attitudes to personal hygiene. This study uses descriptive correlational method using cross-sectional design. The sample technique used in this study is total sampling. The study was conducted in May 2018 with a sample of 80 students at SD Merapi Padang Panjang. Data collection techniques using questionnaires. The statistical test used is chi-squere. The results of this study revealed 53.8% of students' knowledge about personal hygiene was low, 51.2% of students' attitudes about personal hygiene were classified as negative, 55% of students' personal hygiene was bad. There is a significant relationship between knowledge and attitudes to personal hygiene students of Padang Panjang Merapi Elementary School in 2018 with a value of p = 0,000. It is expected that teachers pay more attention to knowledge and attitudes to personal hygiene of elementary students because knowledge and attitudes can have the most influence on health status.